2019
DOI: 10.31014/aior.1994.02.02.41
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Acute Pancreatitis (IAP): The Value of Endoscopic Ultrasound

Abstract: The Journal of Health and Medical Sciences is an Open Access publication. It may be read, copied, and distributed free of charge according to the conditions of the Creative Commons Attribution 4.0 International license.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…In comparison, our study found 52% had pathologies of common bile duct in endoscopic ultrasound who had absolutely normal common bile duct in trans abdominal ultrasound. In fact, in a previous study of our centre, gall bladder and common bile duct microlithiasis and sludge are found to be the main reason behind idiopathic acute pancreatitis 29 .…”
Section: Discussionmentioning
confidence: 78%
“…In comparison, our study found 52% had pathologies of common bile duct in endoscopic ultrasound who had absolutely normal common bile duct in trans abdominal ultrasound. In fact, in a previous study of our centre, gall bladder and common bile duct microlithiasis and sludge are found to be the main reason behind idiopathic acute pancreatitis 29 .…”
Section: Discussionmentioning
confidence: 78%